Regional supply of Eco-tourism and collective learning: An institutional perspective - Rüdiger Wink (European Regional Science Association (ERSA), 2003)
Against the background of increasing knowledge on environmental damages by tourism, environmental-friendly tourism became a remarkable niche in the international market for tourism, in particular high-price segments for advanced tourism. Two aspects primarily impede the supply of environmental-friendly tourism: (1) the spatial dimension of environmental effects, making it necessary to implement a regional strategy on preserving environmental functions and coping with competing demands, (2) the characteristics of environmental-friendly tourism as credence good causing the necessity of signalling or screening strategies to overcome adverse selection. Institutions have been developed on a regional level to come to collective agreements on environmental standards and common labels as tourist regions. But still uncertainty remains on (long-term) cause-effect-relationships between tourism and the regional environment and ways to reconcile demanders' interest and prerequisites of functioning ecosystems. Thus, learning is needed to reduce uncertainty, which means that institutions not only serve to cope with problems of asymmetric distribution of information and strategic uncertainty between individual actors (reallocating knowledge between individuals) but also to increase the knowledge base of the individuals as a whole. The proposed paper will investigate different institutional strategies to create incentives for learning on a regional level by sharing and processing knowledge between single suppliers and demanders of tourism as well as other demanders for environmental functions. Special focus will be directed to the relevance of learning for developing regions often faced with difficulties to obtain the net value of advanced tourism within the region. The methodology is based on an evolutionary institutional model integrating approaches from learning psychology and brain sciences into economic analysis. Although the paper refers to an abstract line of argumentation, the results are illustrated by several examples from developing regions.
Keywords: 330